Image guided particle therapy in CNAO room 2: Implementation and clinical validation. Issue 1 (February 2015) - Fattori, G.; Riboldi, M.; Pella, A.; Peroni, M.; Cerveri, P.; Desplanques, M.; Fontana, G.; Tagaste, B.; Valvo, F.; Orecchia, R.; Baroni, G.
Abstract In this contribution we describe the implementation of a novel solution for image guided particle therapy, designed to ensure the maximal accuracy in patient setup. The presented system is installed in the central treatment room at Centro Nazionale di Adroterapia Oncologica (CNAO, Italy), featuring two fixed beam lines (horizontal and vertical) for proton and carbon ion therapy. Treatment geometry verification is based on robotic in-room imaging acquisitions, allowing for 2D/3D registration from double planar kV-images or 3D/3D alignment from cone beam image reconstruction. The calculated six degrees-of-freedom correction vector is transferred to the robotic patient positioning system, thus yielding automated setup error compensation. Sub-millimetre scale residual errors were measured in absolute positioning of rigid phantoms, in agreement with optical- and laser-based assessment. Sub-millimetre and sub-degree positioning accuracy was achieved when simulating setup errors with anthropomorphic head, thorax and pelvis phantoms. The in-house design and development allowed a high level of system customization, capable of replicating the clinical performance of commercially available products, as reported with preliminary clinical results in 10 patients.